2014
DOI: 10.1007/978-3-662-43948-7_15
|View full text |Cite
|
Sign up to set email alerts
|

Star Partitions of Perfect Graphs

Abstract: Bevern, van, R.; Bredereck, R.; Bulteau, L.; Chen, J.; Froese, V.; Niedermeier, R.; Woeginger, G.Published: 01/01/2014 Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers) Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Question: Is there a partition of the vertices of G in such a way that each part induces a path on three vertices? Bevern et al [26] proved that this problem is N P -complete.…”
Section: Complexity When the Radius Is Fixedmentioning
confidence: 99%
“…Question: Is there a partition of the vertices of G in such a way that each part induces a path on three vertices? Bevern et al [26] proved that this problem is N P -complete.…”
Section: Complexity When the Radius Is Fixedmentioning
confidence: 99%
“…Computing star partitions is known to be NP-hard even on subcubic grid graphs and split graphs [6]. By Proposition 1 in Section 3.2 it follows that Dissolution is also NP-hard on planar graph because grid graphs are planar.…”
Section: Planar Graphsmentioning
confidence: 99%
“…In Gledel and Parreau (2019), it was shown that Continuous-G-Min-Disc-Code for bounded-radius disks is NP-complete. The same proof technique, a reduction from the NP-complete P 3 -Partition-Grid problem van Bevern et al (2014), can be adapted to show the following. Given an instance G of P 3 -Partition-Grid, we construct an instance P G of Continuous-G-Min-Disc-Code as follows.…”
Section: A Ptas For the 1d Unit Interval Casementioning
confidence: 99%